HUBUNGAN OBESITAS TERHADAP DERAJAT NYERI PADA PASIEN LANSIA DENGAN SIMTOM OSTEOARTHRITIS DI POSYANDU LANSIA PUSKESMAS KAMPUNG BARU MEDAN MAIMUN TAHUN 2018 - REZA GUSTIRANDA; LITA SEPTINA (LP2MTBM MAKARIOZ, 2020)
Geriatric patients have multipatological problems, which are more related to chronic degenerative diseases such asosteoarthritis (OA), OA which is associated with an imbalance between damage and repair of joint cartilage and associatedsuch as obesity, weight lifting, trauma, and predisposition genetic. OA in a person can overcome severity Both in clinicalterms such as frills that can use Visual Analogue Scale (VAS) or Western Ontario and McMaster University OsteoarthritisIndex (WOMAC). This research is descriptive analytic using cross sectional design (adding latitude), a study sample OA of37 elderly patients at on elderly posyandu at Kampong Baru Health Center in January to September 2018 that was approvedaccording to inclusion and exclusion criteria. The sampling technique uses the Purposive sampling method, with dataanalysis using the chi-square test. Obesity to the degree of risk of elderly patients with osteoarthritis symptoms obtainedrelated to a significant relationship (p <0.05). Related to the significant relationship between obesity to the elderly in elderlypatients with osteoarthritis symptoms at maternal health services kampung baru medan.